2009
DOI: 10.1111/j.1651-2227.2009.01233.x
|View full text |Cite
|
Sign up to set email alerts
|

A survey of neonatal resuscitation in Spain: gaps between guidelines and practice

Abstract: Equipment availability and knowledge of guidelines of NR does not differ between hospitals independent of their level of care. However, performance during resuscitation and transportation in level III hospitals is in significantly greater acquaintance with internationally recommended NR guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 27 publications
1
34
0
1
Order By: Relevance
“…We found a high level of uniformity on knowledge, skills, and key competencies needed to practice neonatology at a tertiary care level. This is not surprising since medical care of extremely preterm infants and sick newborns is essentially the same across Europe [5,6,7]. The lack of coherence with the ESN Curriculum on specific skills (EEG, suprapubic bladder puncture, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…We found a high level of uniformity on knowledge, skills, and key competencies needed to practice neonatology at a tertiary care level. This is not surprising since medical care of extremely preterm infants and sick newborns is essentially the same across Europe [5,6,7]. The lack of coherence with the ESN Curriculum on specific skills (EEG, suprapubic bladder puncture, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…At the time of completion of our course, the latest edition of the NRP textbook had not yet been released; however, the Simulation has been demonstrated to be a useful tool during the period of residency [15][16][17], but its utility is not limited to those years of training or to inexpert pro-principal changes could be previewed by reading the AAP and AHA guidelines, and many articles anticipated the inclusion of simulation as an educational tool [22]. Recently, we have witnessed the local adaptation of our country to these new international changes, and simulation and debriefing techniques are mentioned with their application to neonatal resuscitation training [23].…”
Section: Discussionmentioning
confidence: 99%
“…Continuous positive airway pressure (CPAP) in the delivery room has gained popularity over the past years, particularly for the preterm population. But its use varies between 50 and 85% across countries, with units setting different gestational age thresholds (anywhere from 24-32 weeks) above which they would attempt CPAP [2,3,5,9]. For those infants who get intubated, 3-45% of units have reported using CO 2 detectors [4,[6][7][8][9].…”
Section: Respiratory Care Management In the Delivery Roommentioning
confidence: 99%
“…Despite evidence-based recommendations on the use of pulse oximetry (PO), oxygen blenders and resuscitation of term infants with room air [1], some units have not yet adopted these practices. Routine use of PO and O 2 blenders ranges from 30 to 100% and 36 to 100% across units, respectively [2,[5][6][7][8][9][10]. Although guidelines recommend preductal saturation measurements, one survey showed that only 37% of units placed their saturation probes correctly [3].…”
Section: Respiratory Care Management In the Delivery Roommentioning
confidence: 99%
See 1 more Smart Citation